Underplanting is a practical silvicultural method for regenerating and diversifying conifer stands in Britain. (30th July 2020) - Stokes, Victoria; Kerr, Gary; Connolly, Thomas
Abstract: There is a strong policy move in Britain to improve forest resilience to climate change by increasing stand structural and species diversity. Although currently little used in Britain, the technique of underplanting allows regeneration and diversification of stands while avoiding some of the disadvantages of clearfelling. Two experiments were examined: (1) the growth and survival of five underplanted conifer species of differing shade tolerance in a shelterwood and (2) compared performance of underplanted and open-grown Douglas-fir seedlings on restocking sites. Underplanted Sitka spruce, Norway spruce, noble fir, European silver fir and Douglas-fir were all able to survive and grow. However increased exposure following overstorey removal resulted in some damage and 'socketing', especially to taller seedlings, particularly Douglas-fir. This may be linked to poor root development when growing under an overstorey. Microclimate conditions on some underplanted sites were more sheltered from extreme climatic conditions, and in some cases this improved survival of Douglas-fir seedlings. However, seedling growth rates were reduced compared with those on open sites probably due to lower light levels. Underplanting may help to improve establishment success of some species, particularly in exposed areas. However, the shelter benefits of underplanting must be carefully balanced against the trade-off with lower light, and underplanting is likely to be more successful where low canopy density is maintained.